Synthesis and Performance of Polyamide Forward Osmosis Membrane for Natural Organic Matter (NOM) Removal - Mazrul Nizam, Abu Seman; L. M., Kei; M. A., Yusoff (World Academy of Science, Engineering and Technology, 2015)
Forward Osmosis (FO) polyamide thin-film composite membranes have been prepared by interfacial polymerization using commercial UF polyethersulfoneas membrane support. Different interfacial polymerization times (10s, 30s and 60s) in the organic solution containing trimesoyl chloride (TMC) at constant mphenylenediamine (MPD) concentration (2% w/v) were studied. The synthesized polyamide membranes then tested for treatment of natural organic matter (NOM) and compared to commercial Cellulose TriAcetate (CTA) membrane. It was found that membrane prepared with higher reaction time (30s and 60s) exhibited better membrane performance (flux and humic acid removal) over commercial CTA membrane.